1992
DOI: 10.3109/10715769209083144
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Sensors for Direct Reagentless Measurement of Superoxide Production by Human Neutrophils

Abstract: Electrochemical sensors based on immobilised cytochrome c or superoxide dismutase for the measurement of superoxide radical production by stimulated neutrophils are described. Cytochrome c was immobilised covalently at a surface-modified gold electrode and by passive adsorption to novel platinised activated carbon electrodes (PACE). The reoxidation of cytochrome c at the electrode surface upon reduction by superoxide was monitored using both xanthine/xanthine oxidase and stimulated neutrophils as sources of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 5 publications
4
59
1
Order By: Relevance
“…On the other hand, addition of catalase increased the signal (Fig. 4D between the rate of the current increase from O 2 •-sensitive gold electrodes and the number of cells seeded was obtained (Chang et al, 2005a(Chang et al, , 2005b, whereas in the present work, and some other studies (McNeil et al, 1992(McNeil et al, , 1995, the response curve was not linear, but showed a saturation behaviour at higher neutrophil loadings, reflecting the attachment of the latter to the electrode surface.…”
Section: Discussioncontrasting
confidence: 40%
“…On the other hand, addition of catalase increased the signal (Fig. 4D between the rate of the current increase from O 2 •-sensitive gold electrodes and the number of cells seeded was obtained (Chang et al, 2005a(Chang et al, , 2005b, whereas in the present work, and some other studies (McNeil et al, 1992(McNeil et al, , 1995, the response curve was not linear, but showed a saturation behaviour at higher neutrophil loadings, reflecting the attachment of the latter to the electrode surface.…”
Section: Discussioncontrasting
confidence: 40%
“…The most developed device is constituted of cytochrome ccoated gold [17][18][19][20][21][22][23][24][25][26][27] or platinized carbon electrode [21,28,29]. Superoxide anion reduces the immobilized ferricytochrome c, which is immediately re-oxidized by the surface-modified electrode at a potential of 15-25 mV vs Ag/AgCl, as illustrated in figure 1.…”
Section: Amperometric Biosensors: Designs and Applications Cytochromementioning
confidence: 99%
“…Another approach for making cytochrome c-coated electrodes consistes to achieve the immobilisation of cytochrome c by passive adsorption on platinized carbon electrode, PACE, as follow: a platinized activated carbon electrode (1 cm 2 area) is immersed in a phosphate buffer solution (pH = 7.4) of cytochrome c (10 mg/ml) and shaked gently for few hours [21]. After this time, the PACE incorporating adsorbed cytochrome c is rinsed throughly and stored in phosphate buffer solution at 5°C.…”
Section: Amperometric Biosensors: Designs and Applications Cytochromementioning
confidence: 99%
See 1 more Smart Citation
“…Calibration of electrodes using xanthine-xanthine oxidase system in vitro Cytochrome c electrodes were prepared using a modi fication of the method of McNeil et al (1992). Electrodes were constructed of platinized carbon electrode (PACE) material (EFCG S type material; E-Tek, Natick, MA, U.S.A.), which was the generous gift of Dr. Calum Mc Neil.…”
Section: Methodsmentioning
confidence: 99%